Extrapolative Morph Design Thinking as an Intangible Ecological Form to Encode the Ecodesign Identity - Chumiran , Mohd Hasni; Zainal Abidin , Shahriman; Anwar , Rusmadiah; Alli , Hassan (Environment-Behaviour Proceedings Journal, 2020)
This paper identifies a new distinction of ecodesign form, where it emerged from the literature case study that most practising designers have not conceived to interpret design research as an ecodesign identity. This research article objective reveals the ecological form creation in the semantics orders. The imaging product digitized an ecological form that was hermeneutically sourced by the literature review process using the heuristic method. It digitized the visual imagery before entering the prescriptive stage. The product imagery therefore digitized some ecodesign characteristics that the intangible ecological form conveyed in the form follows functional perspective; believing to environmentally-friendly product design. Keywords: Form; heuristic method; industrial design; intangible ecological form eISSN: 2398-4287Â© 2020. The Authors. Published for AMER ABRA cE-Bsby e-International Publishing House, Ltd., UK. This is an open access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peerâ€“review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: https://doi.org/10.21834/ebpj.v5iSI3.2538